Extraction, characterization and comparison the components of Eruca vesicaria L and Eruca sativa Mill and study their biological activity - Ghassan Radam Idan AL-Taie; Ahmed A. Ismail; Mostefa Khalid Mohammed; Ziad T I Alkyar; Nagham Thayer Salman (Institute of Computer Science (IOCS), 2024)
In this work high performance liquid chromatography (HPLC) was used to isolate and study the components of plants Eruca sativa and Eruca vesicaria, both are belonging to the family Brassicaceae. The extractions have done using Soxhlet apparatus. However, the result shows that there are some different in the compounds for each. The Eruca extracts are a powerful antioxidant agent and the analysis of both plant samples using the HPLC chromatogram with standard sample shows that the extracts of both plants contains an antioxidant compounds. The antibacterial activities of the extracts were tested against Escherichia coli, Staphylococcus aureus and the activity was good towards the selected bacteria. In addition, the extracts show a good antifungal activity towards candida albicans).